The politics of health systems policies during COVID-19: reflections on experiences from Latin America and the Caribbean - Walter Flores; Alexis Sullivan; Fernando Jerez; Daniela C. Rodríguez (BMC, 2024)
Abstract Politics as the exercise of power always influence public policies-which reflects the multifaceted nature of decision-making-but "using politics" as a motivation for self-serving interests of government leaders and their allies poses problems. This article reviews the impacts of COVID-19 on health systems of the Latin American and Caribbean region from a political lens. We highlight the overriding influence of politics in health policies, weak governance structures that became compromised, exacerbation of corruption, and breakdowns in the communication and trust between governments and their citizens. There are many factors that did not work well-or as expected. For instance, the poor predictive ability of the Global Health Security Index, which showed that pre-pandemic assessments were deeply naive to how health systems evidence and expertise are uniquely vulnerable to politics. We argue that there is an urgent need to rethink health policy and systems frameworks-including metrics-at national and global level. There is also a need for new global health governance arrangements. The expected solidarity and collaboration among countries was trumped by the rich countries practice of gauging essential resources and vaccines and applying health diplomacy to the rest of the world, and the unchecked power of commercial corporations producing essential medical supplies and vaccines.